The Application of International Financial Reporting Standards in the Dairy Horse Breeding in Supply Chain Management - G.A Khabirov; Z.Z Suleymanov; A.M Ableeva; G.A Salimova; E.I Galimova (International Journal of Supply Chain Management, 2019)
The article discusses the prospects for the introduction of the Russian accounting practice of International financial reporting standards (IFRS), the calculation of the fair value of the biological asset of horse breeding organizations under IFRS. A number of methods of calculation of fair value, a technique based on market value and calculation based on the method of profit capitalization and money flow discounting are considered to justify the effectiveness of supply chain management. To prove the necessity and effectiveness of the implementation of IFRS in the production calculations were made on the example of OJSC